Pengaruh lingkungan kerja dan disiplin kerja terhadap kinerja karyawan divisi produksi PT. Magnesium Gosari Internasional Gresik - Laili, Khullatul; Irbayuni, Sulastri (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the effect of work environment and work discipline on the performance of employees in the production division at PT. Magnesium Gosari International Gresik. In this study, the number of samples is 55 workers in the production division at PT. Magnesium Gosari International Gresik. This study retrieves data information using a method by distributing questionnaires to production division workers at PT. Magnesium Gosari International Gresik. The variables determined by the researchers include: the independent variable is the Work Environment (X1) and Work Discipline (X2) and for the dependent variable is Performance (Y). This study uses an analytical model in the form of a Partial Least Square (PLS) model, which is a technique to construct a model that can be assumed when there are several factors. The results of this study indicate that a good work environment and high work discipline can encourage employee performance at PT. Magnesium Gosari International Gresik.